Young Adults’ Loneliness and Depression During the COVID-19 Pandemic: A Moderated Mediation Model - Lv, Fangyan; Yu, Meng; Li, Jie; Tan, Jingbin; Ye, Zhanhang; Xiao, Mengqi; Zhu, Yalin; Guo, Siyuan; Liu, Yanping; Gao, Dingguo (Frontiers in Psychology, 2022)
Since the occurrence of the COVID-19 in December 2019, millions of people have been infected with the disease. The COVID-19 pandemic also produced severe mental health problems, such as loneliness and depression. The present study aimed to examine the mediating role of cognitive reappraisal and moderating role of resilience in the relationship between young adults’ loneliness and depression during the pandemic by adopting a cross-sectional approach. In March 2020, 654 young adults (18-29 years old) were recruited to complete the measures for loneliness, depression, emotion regulation, and resilience. Results showed that loneliness was positively associated with depression (r = .531, p < .001), and that both loneliness and depression were negatively associated with cognitive reappraisal (r = - .348, p < .001; r = -.424, p < .001) and resilience (r = - .436, p < .001; r = - .419, p < .001), but were not associated with expressive suppression (r = .067, p = .087, and r = -.002, p = .961 respectively). The moderated mediation analysis revealed that only cognitive reappraisal partially mediated the relationship between loneliness and depression (b = -.301; Boot 95% CI = -.388, -.215). In addition, the moderated mediation model indicated that resilience moderated the association between loneliness and depression (b = .035, p < .001, Boot 95% CI = .014, .055), while also moderated the impact of cognitive reappraisal on depression (b = - .031, p < .001, Boot 95% CI = - .058, - .005). These findings have practical implications that broaden our understanding of depression in young adults and shed light on how to enhance cognitive reappraisal and resilience as an effective means of combating depression in this age group during the COVID-19 pandemic.